A mini review of communicative language testing - Liao, Linyu; Ye, Shelly Xueting; Yang, Jinsong (Frontiers in Psychology, 2023)
Compared with traditional language testing, which heavily emphasizes psychometric reliability, communicative language testing (CLT), which uses authentic tasks to measure communicative abilities, has long been dominant in language assessment. Given its widely acknowledged advantages and widespread use, CLT has become less controversial in the language assessment field and thus is receiving decreased scholarly attention. However, real-world communication, in which CLT is grounded, evolves over time, suggesting the need to update our understanding of it. To address this need and facilitate the further development of CLT theories and practices, this paper offers an up-to-date review of CLT, including its various approaches, implementation challenges, and suggestions for future research.